Orðaheimur - en fraseologisk begrepsordbok - Jónsson, Jón Hilmar (Nordiske Studier i Leksikografi, 2005)
Orðaheimur is a new lcelandic thesaurus of phrases. It is dividcd into two main parts. The first part is an alphabetized list of 840 concepts with subordinate phrases and idioms. The sceond part contains the 33.000 phrases and idioms from the first part ordered alphabetically by keywords, with references to the concepts in the first part. The phrases and idioms within the entry for each concept are presented in a standardized form and in a fixed order to make searching as easy as possible. The concepts are crossindexed where appropriate, as they often overlap. The list of eoneepts is also translated in to English to make the dictionary more useful for non-native speakers. The topic of this paper is the advantages entailed in this type of lexicographic approach, bearing in mind that users need both syntactic and semantic features when searehing for, and indeed when using phrasal dictionary entries. A conceptually based description of phrases must facilitate the access and demarcation of the target material, and the use of cross-references between concepts further enlarges the scope of enquiry to semantically related phrases and idioms.